Development of an Android-Based Game Using Forward Chaining for Detecting Bullying Among Junior High School Students - Arya Jonathan Trijadi; Astrid Novita Putri (Program Studi Ilmu Komputer, Universitas Pakuan, 2025)
Bullying is an aggressive behavior commonly occurring among junior high school students, with detrimental impacts on both physical and mental health. This research developed an Android-based quiz game to detect bullying using the Forward Chaining method. The application is designed to identify five types of bullying: physical, verbal, direct non-verbal, indirect non-verbal, and cyber. The development process employed the Multimedia Development Life Cycle (MDLC), which includes concept, design, material collection, assembly, testing, and distribution. Testing results indicated that the application is effective in detecting bullying cases, facilitating guidance counselors (BK teachers) in obtaining accurate data, and enhancing student engagement through an interactive approach. This study aims to aid in bullying prevention within schools while serving as a foundation for further development in integrating technology for social intervention and providing opportunities for subsequent research on optimizing game features and developing data-driven interventions.